Changes in serum adropin, salusin alpha and salusin beta, vaspin, and preptin in hyperemesis gravidarum - Dag, Z. O.; Tulmac, O. B.; Isik, Y.; Kisa, U.; Aydin, S. (I R O G Canada, Inc, 2018)
Purpose: To investigate serum levels of adropin, salusin alpha and salusin beta, vaspin, and preptin in pregnant women with hyperemesis gravidarum (HG) and uncomplicated pregnancies. Materials and Methods: Thirty-three pregnant women with HG (group 1) and 30 pregnant women with uncomplicated pregnancies (group 2) who were referred to the University Obstetrics-Gynecology clinic were enrolled in this present study. Fasting serum samples were obtained and measured for adropin, salusin alpha and salusin beta, vaspin, and preptin. The hormones levels were studied by using ELISA method. Results: Statistically significant difference was found between groups 1 and 2 according to adropin, salusin alpha and salusin beta, vaspin, and preptin levels (all p < 0.05). There were increased levels of salusins and adropin and decreased levels of vaspin and preptin in women with HG. Conclusion: This study suggests a possible role of these peptides, which may clarify the etiopathogenesis of HG.
Keywords: Hyperemesis gravidarum; Adropin; Salusin alpha and salusin beta; Vaspin; Preptin